(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Today's life the Artificial intelligence (AI) is one of the key components of students as well as teachers and researchers. In education system artificial intelligence become a backbone and most helpful tools which is playing vital role in higher education system. Artificial intelligence has become one of the biggest challenges facing our education system related to quality of services delivered. It may seems that artificial intelligence become a smart tool for students which can make smart not a alternate of teachers which take lecture and students emotions. Education is one of the most affected fields where the impact of artificial intelligence leads to positive and sometimes negative outcomes. The broad consensus is that effective pedagogy leads to high-quality educational outcomes. Therefore, AI-powered tools and techniques automate tasks, personalize the learning process, and deliver real-time feedback. Chatbots like ChatGPT are one of the beneficial ways to use artificial intelligence in education.